RELIGIOUS MODERATION FOR CONTEMPORARY URBAN MUSLIMS: DEVELOPING A GUIDE FOR UNIVERSITY STUDENTS IN JAKARTA AND BASRA - Nuruddin, Nuruddin; Romdani, Romdani; Sarip, Moh.; Abdullah, Murad Hameed; Arifin, Ahmad; Hafizah, Hafizah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2025)
This research aims to develop a guiding model to assimilate the values of religious moderation among students to ward off extremism in two urban cities: Jakarta, Indonesia, and Basra, Iraq. This research uses the Borg and Gall model design development research method. Data in the study consisted of document data in the form of lecture materials and reference books related to religious moderation in Jakarta and Basra, and data from the needs analysis of students in the two towns associated with the guiding model for understanding the values of religious moderation. This research concludes that the guiding model for understanding the values of religious moderation in the cities of Jakarta and Basra needs to be developed in several ways: efforts to instil values of religious moderation among students in the cities of Jakarta and Basra and efforts to instil the values of religious moderation in students in the cities of Jakarta and Basra. The value of religious moderation is in the aspect of love for the homeland and the state; the value of religious moderation is on the side of tolerance and the prohibition of extremism, and the value of religious moderation is on the side of friendship and avoiding conflict.